2014
DOI: 10.1016/j.apcbee.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Doses and Application Times in Weed Suppression on Different Red Bean Varieties

Abstract: This study was conducted to evaluate the effect of different application times and doses of bentazon on weeds growth in different red bean (Phaseolus calcaratus) cultivars. Three factors were studied in split factorial in the form of a randomized complete block design with three replications. The main factor was red bean cultivar (Naz and Derakhshan), the sub factor was time of herbicide application (one sprayed at the third trifoliate stage and another sprayed 15 days after the first spray), and the sub-sub f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Algumas pesquisas têm relatado que a aplicação dos herbicidas imazamox, bentazon, fomesafen, [bentazon + imazamox] e [fluazifop-p-buthyl + fomesafen] em feijoeiro tem ocasionado fitotoxicidade, porém esses herbicidas são metabolizados pelas plantas e a cultura se recupera em poucos dias após a aplicação (SOLTANI; BOWLEY; SIKKEMA, 2005;FONTES;OLIVEIRIA;GONÇALVES, 2013;ZARGAR;PAKINA;ROMANOVA, 2014;GALON et al, 2017), o que condiz com os resultados encontrados no presente estudo.…”
Section: Resultsunclassified
“…Algumas pesquisas têm relatado que a aplicação dos herbicidas imazamox, bentazon, fomesafen, [bentazon + imazamox] e [fluazifop-p-buthyl + fomesafen] em feijoeiro tem ocasionado fitotoxicidade, porém esses herbicidas são metabolizados pelas plantas e a cultura se recupera em poucos dias após a aplicação (SOLTANI; BOWLEY; SIKKEMA, 2005;FONTES;OLIVEIRIA;GONÇALVES, 2013;ZARGAR;PAKINA;ROMANOVA, 2014;GALON et al, 2017), o que condiz com os resultados encontrados no presente estudo.…”
Section: Resultsunclassified
“…Alguns herbicidas apresentaram as maiores fitotoxicidades aos 7 dias após a aplicação (DAT), com recuperação dos sintomas de injúrias com o passar do tempo, como é o caso do fluazifop-p-buthyl, fomesafen, bentazon, imazamox, bentazon + imazamox e fluazifop-p-buthyl + fomesafen. Algumas pesquisas tem relatado que a aplicação de imazamox, bentazon, fluazifop-p-butil e fomesafen em feijoeiro tem ocasionado injúrias, porém são detoxificadas e a cultura se recupera em poucos dias após a aplicação (Soltani et al, 2005;Nina, 2011;Fontes et al, 2013;Zargar et al, 2014), o que condiz com os resultados encontrados no presente estudo.…”
Section: Resultsunclassified
“…The dose–response study demonstrated that electricity can be used to kill small Tamarix plants. More importantly, it showed that plant response to electricity, like plant responses to numerous herbicides (Boström and Fogelfors, 2002; Zargar et al, 2014), is dependent upon the dose. In our case, the dose was calculated as mA applied over time (i.e., mAh).…”
Section: Discussionmentioning
confidence: 99%